Knowledge Level and Awareness About Calcium Deficiency, Vitamin D Deficiency and Osteoporosis Among Physical Therapy and Rehabilitation School Students - Fatmanur Aybala Koçak; Özge Barut; Emine Eda Kurt; Senem Şaş; Havva Öztürk Durmaz; Figen Tuncay; Hatice Rana Erdem (Türk Osteoporoz Dergisi, 2020)

(untitled)
Objective:To evaluate knowledge and awareness levels about deficiencies of calcium and vitamin D, and osteoporosis among physiotherapy students.Materials and Methods:A questionnaire consisting of 33 questions was applied to the 3rd and 4th grade students of Kırşehir Ahi Evran University Faculty of Medicine, Department of Physical Medicine and Rehabilitation.Results:The study included 106 students with a mean age of 21.5±1.19 years (female/male: 58/48). The students had knowledge about “calcium deficiency”, “vitamin D deficiency”, and “osteoporosis”. Students with knowledge were asked where they got this information. “School” was specified as the most common source of information in all three groups. The students had accurate information about the clinical symptoms of calcium and vitamin D deficiency. Many students knew what to do to prevent osteoporosis. Although many students knew the foods that are rich in calcium and vitamin D, there was a lack of information on the amount of daily necessity. In addition, many students did not know how often to sunbathe for an adequate vitamin D level.Conclusion:It was observed that students’ knowledge and awareness levels about calcium deficiency, vitamin D deficiency, and osteoporosis are quite high. However, students need to be informed more about foods that are rich in calcium and vitamin D, and the duration of sunbathing.